Сучасні підходи до розв'язання задач комп'ютерного зору - Тимчишин, Р.М.; Волков, О.Є.; Господарчук, О.Ю.; Богачук, Ю.П. (Управляющие системы и машины, 2018)
Наведено структурований огляд сучасних методів розв’язання задач комп’ютерного зору, їх переваг та недоліків, і визначення невирішених проблем. Цей напрямок швидко прогресує, що пов’язано зі збільшенням обчислювальної потужності комп’ютерів, а також підключенням до дослідження таких гігантів IT індустрії, як Google і Microsoft. Розглянуто абсолютно різні за своєю природою підходи: підхід на основі нечіткої логіки; підхід на базі згорткових нейронних мереж та глибокого навчання; підхід з використанням детекторів і дескрипторів. Розглядається не тільки точність алгоритмів, але і їх швидкодія та затрати пам’яті, що відіграють важливу роль для вбудованих систем (безпілотних літальних апаратів, мобільних пристроїв, роботизованих та супутникових систем). Цель. Количество наработок в области компьютерного зрения увеличивается экспоненциально и выбор подходящего инструмента — непростая задача. Цель данной статьи — представить структурированный обзор современных технологий компьютерного зрения с их преимуществами и недостатками, а также идентифицировать нерешенные проблемы. Методы. Нечеткая логика, сверточные нейронные сети, детекторы и дескрипторы ключевых точек. Результаты. Теория нечеткой логики вывела распознавание на качественно новый уровень представив новый фреймворк для работы со сложными и неопределенными системами. Введение нечетких множеств второго типа значительно улучшило точность и устойчивость алгоритмов. Основными преимуществами систем на базе нечеткой логики являются использование знаний эксперта и интерпретируемость финальной модели. Сейчас этот метод часто используется для решения задач сегментации и фильтрации изображений. Purpose. The number of developments in the field of computer vision increases exponentially and staying up to date is not an easy task. There is a wide variety of existing approaches and choosing the right one can be difficult. The goal of this paper is to present a structured overview of modern techniques in the field of computer vision with their advantages and disadvantages, and identification of unresolved problems. Accuracy is not the only quality measure considered, we also take speed and memory into account, which is critical for embedded systems (unmanned aerial vehicles, mobile devices, robotic and satellite systems). Methods. Fuzzy logic, convolutional neural networks, feature detectors and descriptors. Results. Fuzzy logic theory has led recognition to a completely new level by presenting a new methodological and algorithmic framework for working with complex and uncertain systems. Introduction of type-2 fuzzy sets has significantly improved accuracy and robustness. Their main advantages are the use of expert’s knowledge and interpretability of fuzzy logic models. Now fuzzy logic is mainly used as a complement for other systems with the aim to improve decision making process by handling the uncertainty. Researchers often employ this technique for solving image segmentation and filtering problems.